Are Redox‐Active Organic Small Molecules Applicable for High‐Voltage (>4 V) Lithium‐Ion Battery Cathodes?. Issue 12 (10th March 2022) - Katsuyama, Yuto; Kobayashi, Hiroaki; Iwase, Kazuyuki; Gambe, Yoshiyuki; Honma, Itaru
Abstract: While organic batteries have attracted great attention due to their high theoretical capacities, high‐voltage organic active materials (> 4 V vs Li/Li + ) remain unexplored. Here, density functional theory calculations are combined with cyclic voltammetry measurements to investigate the electrochemistry of croconic acid (CA) for use as a lithium‐ion battery cathode material in both dimethyl sulfoxide and γ ‐butyrolactone (GBL) electrolytes. DFT calculations demonstrate that CA dilitium salt (CA–Li2 ) has two enolate groups that undergo redox reactions above 4.0 V and a material‐level theoretical energy density of 1949 Wh kg –1 for storing four lithium ions in GBL—exceeding the value of both conventional inorganic and known organic cathode materials. Cyclic‐voltammetry measurements reveal a highly reversible redox reaction by the enolate group at ≈4 V in both electrolytes. Battery‐performance tests of CA as lithium‐ion battery cathode in GBL show two discharge voltage plateaus at 3.9 and 3.1 V, and a discharge capacity of 102.2 mAh g –1 with no capacity loss after five cycles. With the higher discharge voltages compared to the known, state‐of‐the‐art organic small molecules, CA promises to be a prime cathode‐material candidate for future high‐energy‐density lithium‐ion organic batteries. Abstract : Croconic acid (CA) is investigated as a high‐energy‐density organic cathode material for lithium‐ion batteries. Its theoretical energy density is beyond those of most conventional materials thanks to its high‐voltage (>4 V) redox potentials of the two enolate groups. The electrochemical experiments confirm that CA undergoes reversible multi‐electron redox reactions around 4 V, which can be utilized for energy storage.